Linked Labor Market Data: Towards a novel data housing strategy - Hein, Kristine [Verfasser] (My University, 2024)
"The labor market is a domain rich in diverse data structures, both quantitative and qualitative, and numerous applications. This leads to challenges in the domain of data warehouse architecture and linked data. In this context, only a few approaches exist to generate linked data sets. For example, the multilingual classification system of European Skills, Competences, Qualifications, and Occupations (ESCO) and the German Labor Market Ontology (GLMO) serve as prominent examples showcasing the pivotal role of ontologies." (Author‘s abstract; BIBB-Doku)
Keywords: G 1.2 Arbeitsmarkt; 370; Arbeitsmarkt; Arbeitsmarktforschung; Datenaufbereitung; Datenanalyse; Berufsklassifikation; ESCO